PERAN KELUARGA DALAM PEMBELAJARAN PADA MASA PANDEMI COVID-19 - Rusiadi Rusiadi (Cross-border, 2019)
Learning is a teaching and learning activity that determines student success which is usually in learning activities where there is interaction between teachers and students and is carried out face-to-face. However, since the end of 2019, a virus has been found that has attacked Wuhan and its surroundings, also known as the corona virus. The world was shocked by the presence of the virus, many victims fell because this virus is easily transmitted through direct interaction with people infected with the corona virus (covid-19). On March 2, 2020, it was reported that in Indonesia there were 2 confirmed cases of COVID-19. This makes the government take a policy to implement Large-Scale Social Restrictions. This has resulted in learning activities being diverted to learning at home, which during this pandemic is prohibited from crowds and face-to-face learning. Of course this is a challenge for the student's family. the family has a major role during learning at home. The purpose of this paper is to find out the role of the family during the learning period during the covid-19 period. Because family is the closest person to students, especially during the covid-19 pandemic when students are more and more with their families. In this case, it is more directed to SD/MI students.